Islam, State, and Modernity
XXIII, 320 p.
Keywords: This book offers the first comprehensive introduction to one of the most significant Arab thinkers of the late 20th century and the early 21st century: the Moroccan philosopher and social theorist Mohammed Abed al-Jabri. With his intellectual and political engagement, al-Jabri has influenced the development of a modern reading of the Islamic tradition in the broad Arab-Islamic world and has been, in recent years, subject to an increasing interest among Muslims and non-Muslim scholars, social activists and lay men. The contributors to this volume read al-Jabri with reference to prominent past Arab-Muslim scholars, such as Ibn Rushd, al-Ghazali, al-Shatibi, and Ibn Khaldun, as well as contemporary Arab philosophers, like Hassan Hanafi, Abdellah Laroui, George Tarabishi, Taha Abderrahmane; they engage with various aspects of his intellectual project, and trace his influence in non-Arab-Islamic lands, like Indonesia, as well. His analysis of Arab thought since the 1970s as a harbinger analysis of the ongoing “Arab Spring uprising” remains relevant for today's political challenges in the region.